2014
DOI: 10.12691/education-2-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Humor Creator and the Audience - A Multi-dimensional Model Supported by In-vivo Methodology

Abstract: The purpose of this study was to reevaluate the multi-dimensional model of humor creation, which is comprised of three dimensions: humor motivation, humor cognition, and humor communication, using in vivo (natural setting) methodology. Thirty-four lecturers from colleges and universities completed a questionnaire. Additionally, 1530 students observed these lecturers and evaluated their sense of humor. Judges also evaluated the degree of humor in 750 video clips excerpted from 91 filmed lessons taught by the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Judges had to be blind to any characteristic of the humor producers. This excludes studies in which judges observed participants in the lab or on video (e.g., Inglis, Zach, & Kaniel, 2014).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Judges had to be blind to any characteristic of the humor producers. This excludes studies in which judges observed participants in the lab or on video (e.g., Inglis, Zach, & Kaniel, 2014).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…There is a widespread agreement that humour is a complex, multidimensional social phenomenon (e.g., Robinson & Smith-Lovin 2001;Lockyer & Pickering 2008;Inglis et al 2014). Its content ranges from humour creativity and production, humour appreciation, comprehension and enjoyment, humour expression, use of humour in everyday social situations, use of humour for coping, etc.…”
Section: Measurementsmentioning
confidence: 99%